Essentials of qualitative meta-analysis - Timulak, Ladislav; Creaner, Mary (Essentials of qualitative methods, 2023)
"This book is a step-by-step guide to conducting qualitative meta-analysis (QMA), a flexible and generic method that synthesizes the findings of several research studies investigating similar phenomena"-- Provided by publisher.